Implementasi E-Pajak sebagai Strategi Peningkatan Kepatuhan Wajib Pajak - Intan Nuraini; Nikita Sheila Pasha; Karmila Nuralifah Kadir (Pusat Riset dan Inovasi Nasional, 2025)
Taxes are responsible for providing services and development to the community because the country’s main income comes from taxes. However, the low level of taxpayer compliance is a significant challenge. This study aims to examine how the implementation of e-tax improves taxpayer compliance in Indonesia. The researcher used a descriptive qualitative approach method by analyzing various previous journal studies. The results of the study indicate that among the many benefit provided by e-tax, there are still obstacles in the implementation of e-tax among the taxpayer. Public awareness which is still minimal is the main challenge in implementing taxes electronically. Limitations and gaps in infrastructures that affect internet connections in their implementation make it difficult to access the DJP Online Portal. Technological developments also increase vulnerability to security, the government is required to guarantee the security of taxpayer financial data. The influence of tax implementation that affects taxpayer compliance with E-Filling. Tax payment not only covers building but also law enforcement in the field of motor vehicle taxation. Currently the E-Samsat system has begun to be implemented which provides convenience in the tax payment process. To optimize this e-tax system, there are several strategies in the form of developing and improving the e-Filling system, providing comprehensive tax services. With a structured approach, e-tax has great potential to support digital tax reform and can improve administrative efficiency and also strengthen the country’s fiscal foundation as a whole.